Key Plant, Key Pest: Juniper (Juniperus sp.) - Juanita Popenoe; Jacqueline Bourdon; Caroline Roper Warwick; Heqiang Huo (EDIS, 2019)
This series of Key Plant, Key Pests publications is designed for Florida gardeners, horticulturalists, and landscape professionals to help identify common pests associated with common Florida flora. This seven-page publication, the ninth in the Key Plant, Key Pests series, helps identify the most common pests found on Juniper, with information and general management recommendations for bagworms, eriophyid mites, scale, spider mites, webworm, mushroom root rot, needle blight, Rhizoctonia web blight, tip blight, and wet root rot diseases. Written by Juanita Popenoe, Jacqueline Bourdon, Caroline R. Warwick, and Alfred Huo and published by the UF/IFAS Environmental Horticulture Department. http://edis.ifas.ufl.edu/ep570